Cyber Security @ Higher Education – Developing a Preventive Model for Cyber Attack (S/O 13598) - Ali, Hassan; Othman, Zaleha; Abd Rahim, Nazahah; Abdul Hamid, Fathilatul Zakimi (UUM, 2019)
Cyber-attacks have increased significantly in the 21st centuries. Universities, particularly are currently susceptible to cyber-attacks. Facing the dilemma of getting the right balance between sharing education-based system and data protection, universities commonly struggle with cyberattacks. Some even view that open access system, a commonly universities practices, are most vulnerable to cyber-attacks. Previous studies found lack of security is one of the main caused for cyberattack. With everything from personal information to research information and other high value information of its stakeholders, it is imperative that universities develop cyber security model, relevant to protect data breaches via cyberspace. A qualitative study was conducted to examine the threats and prevention measures to the threats from the perspective of cyber security. Specifically, through a case study approach, this study gains an in-depth understanding of the types of cyberattacks and preventive model for cyberattacks at higher institution, namely UUM. The prevention model is useful for practitioners and academia, as the model is a wayfarer for universities and practitioners alike to prevent future damages due to cyber-attack. In addition, the outcome of the study is useful in a way that it contributes to practice implication, i.e Malaysian higher institutions risk management ahead of time in respect of cybersecurity.